Leadership in Action : In Focus - Leader Development - Personal Lives, Powerful Lessons - Ohlott, Marian N. Ruderman. Patricia J. (Center for Creative Leadership, 2003)
Most leaders say they get their most influential and effective developmental training on the job. Too often, however, these same leaders discount what can be learned from experiences outside of work.